Do Sharia Banks Disclose More? (An Empirical Study of Indonesian Banking Sector) - Ristiani Puji Lestari; Zuni Barokah (The Indonesian Journal of Accounting Research, 2016)
Abstract : This study aims to investigate the extent of corporate governance reporting practices in the Indonesian banking sector. Specifically, it seeks to address whether firm-specific characteristics and sharia identity determine the extent of voluntary corporate governance disclosures. The finding shows that larger companies and ones with a higher level of debt tend to provide greater disclosure of corporate governance information. However, higher profitability, as well as sharia identity, do not seem to provide a higher level of disclosure compared to the conventional ones. These findings lead to an interesting question of whether sharia identity matters in the corporate governance disclosure of banking industry.Abstract : Penelitian ini bertujuan untuk mengetahui sejauh mana praktik pelaporan corporate governance di sektor perbankan Indonesia. Secara studi ini menguji apakah karakteristik spesifik perusahaan dan identitas syariah menentukan tingkat pengungkapan tata kelola perusahaan secara sukarela. Temuan menunjukkan bahwa perusahaan besar dan perusahaan dengan tingkat utang yang lebih tinggi cenderung memberikan pengungkapan yang lebih besar atas informasi tata kelola perusahaan. Namun, profitabilitas yang lebih tinggi, serta identitas syariah, tampaknya tidak memberikan tingkat pengungkapan yang lebih tinggi dibandingkan dengan yang konvensional. Temuan ini mengarah pada pertanyaan menarik tentang apakah identitas syariah penting dalam pengungkapan tata kelola perusahaan industri perbankan.